A high-performance PEM fuel cell with ultralow platinum electrode via electrospinning and underpotential deposition. (10th August 2017) - Hong, Shaojing; Hou, Ming; Zhang, Hongjie; Jiang, Yongyi; Shao, Zhigang; Yi, Baolian
Abstract: A novel PEMFC electrode (E-U electrode) with ultralow platinum is prepared by electrospinning and underpotential deposition techniques. The platinum skin (Ptskin ) is in situ deposited on the surface of Pd nanoparticle in the electrospun Pd/C catalyst layer. The energy-dispersive X-ray spectroscopy (EDS) mapping of the cross-section of a single fiber confirms that the distribution of Pd/C@Ptskin catalysts and Nafion ® ionomer matches well in the E-U electrode. The high porosity and large electrochemical surface area (ECSA) of the E-U electrode mitigates the oxygen transfer resistance. The peak power density of the E-U electrode arrives at 0.62 W cm −2 with a Pt loading of 19 μg cm −2, which is higher than that of the conventional electrode (0.55 W cm −2 ) with a Pt loading of 100 μg cm −2 . The degradation rate of peak power density of the E-U electrode is only 4.8% after accelerated stability test (AST) for 30000 cyclic voltammetry (CV) cycles, demonstrating a better durability than that of the conventional electrode. The enhanced durability of the E-U electrode is attributed to nanofiber structure and interaction between Pd and Pt in the Pd/C@Ptskin catalyst.